Badge of Honor or Scarlet Letter? Unpacking Investors' Judgment of Entrepreneurs' Past Failure - Diego Zunino; Mirjam (C.M.) van Praag; Gary Dushnitsky (Tinbergen Institute, 2017)
Research shows that most ventures fail, yet it has devoted limited attention to the consequences of entrepreneurs' past failure for investors' decisions. Our motivating insight is that failure can be due to bad luck, lack of skill or both. Therefore, failure conveys ambiguous information about skill. We predict that investors will discount entrepreneurs that experienced past failure. However, in the presence of a signal of skill, the magnitude of the failure discount is reduced. We test our predictions using an online experiment where respondents are potential investors in seed stage ventures via equity crowdfunding. Respondents evaluate a realistic investment opportunity in a between-subjects design, where we decompose the effect of failure into luck and skill. Our results indicate that investors discount entrepreneurs who have experienced failure. Past failure in the presence of a signal of skill, however, is not discounted. The findings indicate no discount of failure based on the “failed” label only. Overall, our analysis sheds light on the rationality of investors. In a world where entrepreneurial failure is prevalent, we find that investors are sensitive to its core drivers: luck and skill.
Keywords: G32; G24; L26; 330; entrepreneur; venture; failure; luck; skill; investors; crowdfunding; experiment